QUANTITATIVE AND QUALITATIVE ANALYSIS OF SAPONINS IN DIFFERENT PLANT PARTS OF Chlorophytum borivilianum - RAJINDER KAUR; SAROJ ARORA; A.K. THUKRAL (International Journal of Pharma and Bio Sciences, 2015)
Chlorophytum borivilianum is commonly known as safed musli and is sold all over the world for its medicinal values. Tubers of this plant are used to cure reproductive disorders and studies indicate that saponins are the main compounds that are responsible for its therapeutic values. In the present investigation, saponin content and type of saponins in the tubers (without peels), peels of tubers, leaves and seeds were estimated using standard methods. Thin layer chromatography (TLC) was used to identify the types of saponins. Maximum percent yield of crude saponins was found in peel methanol extract, while least saponin content was found in tuber water extract. TLC studies confirmed the presence of furostanol and spirostanol saponins in Chlorophytum borivilianum.